Explaining the Approach of Gender Justice in Urban Spaces Case Study: Urban Space of Imam Rasht Sister Complex - Hamid Pour hossein Roshan; Mohammadreza Pourjafar; Seddighe Aliakbari (برنامه‌ریزی توسعه شهری و منطقه‌ای, 2019)
The physical changes having taken place after the development of the shrine of Imam Reza's sister in Rasht have led to changes in the types of users and reducing the use of space by women. The main purpose of this study was to detect the reasons for the change and the reduction of gender equality in the space of Sister of Imam Reza in Rasht and changes in that space after the implementation of new development plan. The methodology of this study is critical - quality. In order to reach a proper understanding and explanation, Fairclough's critical discourse analysis approach was used to analyze the data and provide the ultimate theory. Based on qualitative- targeted sampling and theoretical saturation criterion, twenty-five women 20 to 40 years from Saghrysazan and Motahari Rasht district participated in this study and their perception of the urban space of Sister of Imam Rashtwas studied and analyzed. Using "critical discourse analysis" and analyzing the findings, which consists of three levels of description (disclosure statements and the content appearing), interpretation (interaction between the interviewer and texture) and determination (of two strains structures and discourse) can be linked to the analysis of the interviews (bed space) and background (macro structures) and provided the possibility of more radical explanations for researchers. By insisting on consideration of Iran's patriarchal structures in the designing of urban spaces,the results of the study were obtained.